Influence of the addition of SiO2 nanoparticles to a hybrid coating applied on an AZ31 alloy for early corrosion protection - Peres, R. N.; Cardoso, E. S.F.; Montemor, M. F.; de Melo, H. G.; Benedetti, A. V. [UNESP]; Suegama, P. H. (Elsevier, 2016)
This work aims to investigate the corrosion resistance of AZ31 magnesium alloy protected by hybrid films based on tetraethylorthosilane (TEOS) and (3-glycidoxypropyl)trimethoxysilane (GPTMS) with the addition of different amounts of SiO2 nanoparticles. The electrochemical techniques used to evaluate the corrosion resistance in 0.1Â molÂ ll−Â 1 NaCl electrolyte were open circuit potential (EOC) measurements and electrochemical impedance spectroscopy (EIS), which diagrams were fitted using equivalent electrical circuits (EEC). Surface and cross-section analyses of the bare and coated samples were performed by means of scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) before and after electrochemical studies. The results showed that the coatings protected the Mg alloy against corrosion, and that the addition of the nanoparticles improves the corrosion resistance. The morphological characterization showed, for the coated systems, the presence of corrosion products adhered to the metal surface, a process that seems to be hindered in the presence of the SiO2 nanoparticles. The results demonstrate that an optimum amount of nanoparticles must be added to the coating in order to optimize the anticorrosion protection and that only early stages protection can be achieved.
Keywords: AZ31 alloy; EIS; Hybrid coating; Morphological characterization